La mediazione della Santa Sede nel processo di normalizzazione delle relazioni bilaterali cubano-statunitensi (Stato, Chiese e pluralismo confessionale, 2024)
The mediation of the Holy See in the process of normalization of Cuban-American bilateral relations ABSTRACT: This article aims to illustrate the fundamental stages and final moments of the singular and complex mediation conducted by the Holy See in the Cuban-American dispute, whose greatest success was the signing in the Vatican in 2014 of a protocol for the normalization of relations bilateral agreements interrupted in the aftermath of the Castro Revolution. In particular, the specificity, in terms of diplomatic dynamics, of this pontifical initiative is analysed, which inaugurated a new phase of negotiations in the stagnant talks that had already begun secretly in Canada between the two parties in 2011. Finally, the system of agreements of medium level concluded between the parties after the re-establishment of normal diplomatic channels, achieved thanks to the proactive role of the Pope and Vatican diplomacy.SOMMARIO: 1. L’attitudine della Santa Sede nell’affaire cubano. Prodromi e primi segnali di disgelo - 2. Lo stallo dei negoziati tra Washington e L’Avana e l’intervento vaticano. La proposta di facilitazione di Papa Francesco - 3. Portata e natura dell’iniziativa pontificia: ‘mediazione’ o ‘buoni uffici’? - 4. Conclusione dell’accordo e ripristino di rapporti diplomatici e bilaterali - 5. Notazioni finali.